Inhibition of the HV1 voltage-gated proton channel compromises the viability of human polarized macrophages in a polarization- and ceramide-dependent manner - Kovacs, Tamas; Cs. Szabo, Bence; Kothalawala, Rosemary Chandrakanthi; Szekelyhidi, Virag; Nagy, Peter; Varga, Zoltan; Panyi, Gyorgy; Zakany, Florina (Frontiers in Immunology, 2024)
The human voltage-gated proton channel (HV1) provides an efficient proton extrusion pathway from the cytoplasm contributing to the intracellular pH regulation and the oxidative burst. Although its pharmacological inhibition was previously shown to induce cell death in various cell types, no such effects have been examined in polarized macrophages albeit HV1 was suggested to play important roles in these cells. This study highlights that 5-chloro-2-guanidinobenzimidazole (ClGBI), the most widely applied HV1 inhibitor, reduces the viability of human THP-1-derived polarized macrophages at biologically relevant doses with M1 macrophages being the most, and M2 cells the least sensitive to this compound. ClGBI may exert this effect principally by blocking HV1 since the sensitivity of polarized macrophages correlates well with their HV1 expression levels; inhibitors of other macrophage ion channels that may be susceptible for off-target ClGBI effects cause no viability reductions; and Zn2+, another non-specific HV1 blocker, exerts similar effects. As a potential mechanism behind the ClGBI-induced cell death, we identify a complex pH dysregulation involving acidification of the cytoplasm and alkalinization of the lysosomes, which eventually result in membrane ceramide accumulation. Furthermore, ClGBI effects are alleviated by ARC39, a selective acid sphingomyelinase inhibitor supporting the unequivocal significance of ceramide accumulation in the process. Altogether, our results suggest that HV1 inhibition leads to cellular toxicity in polarized macrophages in a polarization-dependent manner, which occurs due to a pH dysregulation and concomitant ceramide overproduction mainly depending on the activity of acid sphingomyelinase. The reduced macrophage viability and plausible concomitant changes in homeostatic M1-M2 balance could contribute to both the therapeutic and potential side effects of HV1 inhibitors that show great promise in the treatment of neuroinflammation and malignant diseases.